Пораките на цивилната религија во државниoт амблем и знаме на Советскиот Сојуз - Civil Religious Messages Encoded in the State Emblem and Flag of the Soviet Union - Anne Platoff (Македонски хералд - Macedonian Herald, 2023)
West’s definition provides a basis for the examination of state symbols as part of a broader framework of political culture and societal norms.  Modern states equip themselves with a set of symbols that, typically, are then incorporated into a civil religious culture which reflects the values of the state.  Inherent to these symbols are messages transmitted from the state to the citizenry that are intended to remind the citizen of their obligations to their country.  This article will discuss one such symbol set – that of the Union of Soviet Socialist Republics.  The intent is to examine visual state symbols, consider the meaning attributed to these symbols, and demonstrate how the symbols were used to convey civil religious messages to citizens of the Soviet Union.  While the USSR is no longer a state, an examination of its symbols is useful to the study of symbols in civil religion for several reasons.  First, it stands as a case study of a state with a well-developed propaganda system where symbols were heavily used throughout the society.  Next the USSR stands as an example where, despite sustained efforts to forge a shared identity through civil religious practice, the state failed to preserve the union allowing its fifteen republics to go their separate ways.  Finally, the case of the Soviet Union is particularly interesting because its symbols continue to have relevance decades after the breakup of the USSR.